In silico/vitro Study of Antibacterial Effects of Non-toxic Cinnamic Amidoesters on Artemia salina - Almeida-Júnior, Alexandre; da Silva Souza, Helivaldo Diógenes; de Sousa, Abraão Pinheiro; Oliveira Dantas, Maria Vitória; Sampaio, Fábio Correia; de Sousa Luis, José Alixandre; da Silva Rodrigues-Junior, Valnês; Barbosa-Filho, José Maria; Fiss, Gabriela Fehn; de Athayde-Filho, Petrônio Filgueiras (Current Organic Chemistry, 2025)
According to the PLOS Neglected Tropical Diseases Journal, infection caused by the Gram-negative bacterium Escherichia coli is a neglected tropical disease. Staphylococcus aureus is the most dangerous Gram-positive bacterium among staphylococcal bacteria. Moreover, resistance to Mycobacterium tuberculosis is an urgent public health issue. In this sense, cinnamic acid and acetamide derivatives have been used as strategic nuclei in the design of antimicrobial agents. With the aim of investigating whether antibacterial activity is improved with the junction of cinnamic and acetamide nuclei, cinnamic amidoesters were planned and evaluated as potential antibacterial agents. In silico (ADMET test and molecular docking) and in vitro (antibacterial and antituberculosis evaluation, and toxicity on Artemia salina larvae) studies were performed. Twelve cinnamic amidoesters were synthesized, which present positive characteristics for possible drug candidates, and showed subtle activity against E. coli, however, against S. aureus, unsubstituted and para-substituted compounds (R3 = H, Me, Cl, Br) showed significant activity, with MIC = 156.25-625 µg/mL-1. Only one para-substituted compound (R3 = Bu) showed discrete activity against M. tuberculosis, with MIC = 200 µM. For the most active compounds against S. aureus, the molecular docking study demonstrated affinity with the TtRNA enzyme, which plays a central role in the assembly of amino acids into polypeptide chains. The most active compounds against S. aureus and M. tuberculosis were non-toxic on A. salina, with LC50 > 1000 µg/mL-1. According to in silico/vitro studies, the non-toxic compound 5h (R3 = Cl) stands out as a potential antibacterial agent for further studies.
Keywords: Artemia salina